In this chapter, we provide RD Sharma Class 10 Ex 9.5 Solutions Chapter 9 Arithmetic Progressions for English medium students, Which will very helpful for every student in their exams. Students can download the latest RD Sharma Class 10 Ex 9.5 Solutions Chapter 9 Arithmetic Progressions pdf, Now you will get step by step solution to each question.

Textbook | NCERT |

Class | Class 10 |

Subject | Maths |

Chapter | Chapter 9 |

Chapter Name | Arithmetic Progressions |

Exercise | 9.5 |

Category | RD Sharma Solutions |

Table of Contents

**RD Sharma Solutions for Class 10 Chapter** **9**** Arithmetic Progressions** Ex 9.5 Download PDF

**Arithmetic Progressions**Ex 9.5 Download PDF

**Chapter 9: Arithmetic Progressions Exercise 9.5**

**Question: 1**

Find the sum of the following arithmetic progressions:

(i) 50, 46, 42, … to 10 terms

(ii) 1, 3, 5, 7, … to 12 terms

(iii) 3, 9/2, 6, 15/2, … to 25 terms

(iv) 41, 36, 31, … to 12 terms

(v) a + b, a – b, a – 3b, … to 22 terms

(vi) (x – y)^{2}, (x^{2} + y^{2}), (x + y)^{2}, to 22 tams

(viii) – 26, – 24, – 22, …. to 36 terms

**Solution:**

In an A.P let first term = a, common difference = d, and there are n terms.

Then, sum of n terms is,

(i) Given progression is,

50, 46, 42 to 10 term.

First term (a) = 50

Common difference (d) = 46 – 50 = – 4

n^{th }term = 10

= 5{100 – 9.4}

= 5{100 – 36}

= S × 64

∴ S_{10} = 320

(ii) Given progression is, 1, 3, 5, 7, …..to 12 terms

First term difference (d) = 3 – 1 = 2 n^{th} term = 12

= 6 × {2 + 22} = 6.24

∴ S_{12} = 144.

(iii) Given expression is 3, 9/2, 6, 15/2, … to 25 terms

First term (a) = 3

Common difference (d) = 9/2 – 3 = 3/2

Sum of n^{th} terms S_{n}, given n = 25

(iv) Given expression is, 41, 36, 31 to 12 terms.

First term (a) = 41

Common difference (d) = 36 – 41 = – 5

Sum of n^{th} terms S_{n}, given n = 12

(v) a + b, a – b, a – 3b to 22 terms

First term (a) = a + b

Common difference (d) = a – b – a – b = -2b

Sum of n^{th} terms S_{n} = n/2{2a(n – 1). d}

Here n = 22

S_{22} = 22/2{2.(a + b) + (22 – 1). -2b}

= 11{2(a + b) – 22b)

= 11{2a – 20b}

= 22a – 440b

∴S_{22} = 22a – 440b

(vi) (x – y)^{2},(x^{2} + y^{2}), (x + y)^{2},… to n terms

First term (a) = (x – y)^{2}

Common difference (d) = x^{2} + y^{2} – (x – y)^{2}

= x^{2} + y^{2} – (x^{2} + y^{2} – 2xy)

= x^{2} + y^{2} – x^{2} + y^{2} + 2xy

= 2xy

Sum of n^{th} terms S_{n} = n/2{2a(n – 1). d}

= n/2{2(x – y)^{2} + (n – 1). 2xy}

= n{(x – y)^{2} + (n – 1)xy}

∴ S_{n} = n{(x — y)^{2} + (n — 1). xy)

(viii) Given expression -26, – 24. -22, to 36 terms

First term (a) = -26

Common difference (d) = -24 – (-26)

= -24 + 26 = 2

Sum of n tams S_{n} = n/2{2a + (n – 1)d)

Sum of n tams S_{n} = 36/2{2. -26 + (36 – 1)2}

= 18[-52 + 70]

= 18.18

= 324

∴ S_{n} = 324

**Question: 2**

Find the sum to n tam of the A.P. 5, 2, –1, – 4, –7, …

**Solution:**

Given AP is 5, 2, -1, -4, -7, …..

a = 5, d = 2 – 5 = -3

S_{n} = n/2{2a + (n – 1)d}

= n/2{2.5 + (n – 1) – 3}

= n/2{10 – 3(n – 1)}

= n/2{13 – 3n)

∴ S_{n} = n/2(13 – 3n)

**Question: 3**

Find the sum of n terms of an A.P. whose the terms is given by an = 5 – 6n.

**Solution:**

Given nth term a_{n} = 5 – 6n

Put n = 1, a_{1} = 5 – 6.1 = -1

We know, first term (a_{1}) = -1

Last term (a_{n}) = 5 – 6n = 1

Then S_{n} = n/2(-1 + 5 – 6n)

= n/2(4 – 6n) = n/2(2 – 3n)

**Question: 4**

If the sum of a certain number of terms starting from first term of an A.P. is 25, 22, 19, … is 116. Find the last term.

**Solution:**

Given AP is 25, 22, 19, ……….

First term (a) = 25, d = 22 – 25 = -3.

Given, S_{n} = n/2(2a + (n – 1)d)

116 = n/2(2 × 25 + (n – 1) – 3)

232 = n(50 – 3(n – 1))

232 = n(53 – 3n)

232 = 53n – 3n^{2}

3n^{2} – 53n + 23^{2} = 0

(3n – 29)(n – 8) = 0

⟹ a_{g} = 25 + (8 – 1) – 3

∴ n = 8, a_{g} = 4

= 25 – 21 = 4

**Question: 5**

(i) How many terms of the sequence 18, 16, 14, … should be taken so that their

(ii) How many terms are there in the A P. whose first and fifth terms are -14 and 2 respectively and the sum of the terms is 40?

(iii) How many terms of the A.P. 9, 17, 25, . must be taken so that their sum is 636?

(iv) How many terms of the A P. 63, 60, 57, … must be taken so that their sum is 693?

**Solution:**

(i) Given sequence, 18, 16, 14, …

a = 18, d = 16 – 18 = -2.

Let, sum of n terms in the sequence is zero

S_{n} = 0

n/2(2a + (n. – 1)d) = 0

n/2(2.18 + (n – 1) – 2) = 0

n(18 – (n – 1)) = 0

n(19 – n) = 0

n = 0 or n = 19

(ii) ∵ n = 0 is not possible.

Therefore, sum of 19 numbers in the sequence is zero.

Given, a = -14, a 5 = 2

a+ (5 – 1)d = 2

-14 + 4d = 2

4d = 16 ⟹ d = 4

Sequence is -14, -10, -6, -2, 2, ………..

Given S_{n} = 40

40 = n/2{2(-14) + (n – 1)4}

80 = n(-28 + 4n – 4)

80 = n(-32 + 4n)

4(20) = 4n(-8 + n)

n^{2} – 8n – 20 = 0

(n – 10)(n + 2) = 0

n = 10 or n = -2

Sum of 10 numbers is 40 (Since -2 is not a natural number)

(iii) Given AP 9. 17, 25, ………………

a = 9, d = 17 – 9 = 8, and S_{n} = 636

636 = n/2(2.9 + (n – 1)8)

1272 = n(18 – 8 + 8n)

1272 = n(10 + 8n)

2 × 636 = 2n(5 + 4n)

636 = 5n + 4n^{2}

4n^{2} + 5n – 636 = 0

(4n + 53)(n – 12) = 0

∴ n = 12 (Since n (-53)/4 is not a natural number)

Therefore, value of n is 12.

(iv) Given AP, 63, 60, 57, ………….

a = 63, d = 60 – 63 = -3

S_{n} = 693

S_{n} = n/2(2a + (n – 1)d)

693 = n/2(2.63 + (n. – 1) – 3)

1386 = n(126 – 3n + 3)

1386 = (129 – 3n)n

3n^{2} – 129n + 1386 = 0

n^{2} – 43n + 462 = 0

n = 21, 22

∴ Sum of 71 or 77 tern is 693

**All Chapter RD Sharma Solutions For Class10 Maths**

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment on the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good